Self-Consolidated Concrete-to-Conductive Concrete Interface: Assessment of Bond Strength and Mechanical Properties - EL-Afandi, Mohammed (2023)
In this paper, the mechanical properties and bond strength of composite samples that consist of a conductive concrete (CC) layer and a self-consolidated concrete (SCC) layer are investigated. The bond strength study includes two parameters: (1) surface preparation and (2) casting and testing directions. The surface preparation study shows that, compared to the other methods in this study, the shear key method is the most suitable surface preparation method to fully utilize the CC in a composite. Moreover, the casting direction study reveals that the strength is heavily dependent on the type of test used along with CC’s layer positioning. The flexural strength study confirms that positioning the CC mix in the tensile region is beneficial since it can increase the flexural strength of a structure because of the hybrid steel fibers included in the mixture. Finally, different codes/specifications and published theoretical results are used to predict the CC’s mechanical properties, and the predictions are not as accurate as the SCC predictions, which can be attributed to the presence of conductive fillers in the CC mix.